Correlación del diagnóstico cito-histológico en nódulos tiroídeos año 2005. Indicador de calidad - Moyano S., Leonor; Carreño T., Laura; Niedman E. , Juan Pablo; Pineda B., Pedro; Corco R., Carla; Novoa E., Sebastián (Revista Hospital Clínico Universidad de Chile, 2007)
The fine-needle aspirates are used as the first step in the diagnostic management of thyroid nodules, they are considered cost-effective compared with the other approaches. During 2005 we studied 47 patients with cytology in the preoperative. We compared the FNAB results with the biopsy of the specimen to establish the accuracy of this method. The diagnosis of papillary carcinoma was correctly made in 18 of 47 histologically proven cases. There were no false positive cases. Of the 20 negative cases, 13 had benign diseases; 1 was a false negative with a follicular carcinoma; 3 cases had papillary microcarcinomas and 3 minimally invasive follicular carcinomas. The sensibility and specificity was 100% and 72% respectively. The positive predictive value was 100% and negative predictive value 65%. PAAF of the thyroid gland proved to be an excellent strategy in the preoperative diagnosis for the management of the thyroid nodules.